Interference with ethylene perception at receptor level sheds light on auxin and transcriptional circuits associated with the climacteric ripening of apple fruit (Malus x domestica Borkh.). (5th October 2016) - Tadiello, Alice; Longhi, Sara; Moretto, Marco; Ferrarini, Alberto; Tononi, Paola; Farneti, Brian; Busatto, Nicola; Vrhovsek, Urska; Molin, Alessandra dal; Avanzato, Carla; Biasioli, Franco; Cappellin, Luca; et al.
Summary: Apple ( Malus x domestica Borkh.) is a model species for studying the metabolic changes that occur at the onset of ripening in fruit crops, and the physiological mechanisms that are governed by the hormone ethylene. In this study, to dissect the climacteric interplay in apple, a multidisciplinary approach was employed. To this end, a comprehensive analysis of gene expression together with the investigation of several physiological entities (texture, volatilome and content of polyphenolic compounds) was performed throughout fruit development and ripening. The transcriptomic profiling was conducted with two microarray platforms: a dedicated custom array (iRIPE) and a whole genome array specifically enriched with ripening‐related genes for apple (WGAA). The transcriptomic and phenotypic changes following the application of 1‐methylcyclopropene (1‐MCP), an ethylene inhibitor leading to important modifications in overall fruit physiology, were also highlighted. The integrative comparative network analysis showed both negative and positive correlations between ripening‐related transcripts and the accumulation of specific metabolites or texture components. The ripening distortion caused by the inhibition of ethylene perception, in addition to affecting the ethylene pathway, stimulated the de‐repression of auxin‐related genes, transcription factors and photosynthetic genes. Overall, the comprehensive repertoire of results obtained here advances the elucidation of the multi‐layered climacteric mechanism of fruit ripening, thus suggesting a possible transcriptional circuit governed by hormones and transcription factors. Significance Statement: Apple fruit ripening is largely mediated by ethylene. Interference at the receptor level by an antagonist modifies both the transcriptional and metabolic patterns. Our correlation network analysis showed specific interactions between particular transcripts and fruit texture, aromatic VOCs and polyphenolic compounds. Gene de‐repression and regulatory activations were linked to regulatory circuits that involved auxin, ethylene and transcription factors.